2020
DOI: 10.26434/chemrxiv.12083907.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined Molecular Graph Neural Network and Structural Docking Selects Potent Programmable Cell Death Protein 1/Programmable Death-Ligand 1 (PD-1/PD-L1) Small Molecule Inhibitors

Abstract: The Programmable Cell Death Protein 1/Programmable Death-Ligand 1 (PD-1/PD-L1) interaction is an immune checkpoint utilized by cancer cells to enhance immune suppression. There exists a huge need to develop small molecules drugs that are fast acting, cheap, and readily bioavailable compared to antibodies. Unfortunately, synthesizing and validating large libraries of small-molecule to inhibit PD-1/PD-L1 interaction in a blind manner is a both time-consuming and expensive. To improve this drug discovery pipeline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For instance, a retrospective analysis based on random decoys found that a ML-based SF (MIEC-SVM) was much more predictive than a classical SF (Autodock4.2) on the ALK target, which was exactly what was later observed prospectively [8]. This is not the only ML-based SF reporting excellent prospective SBVS results without any use of PM decoys [14,34]. It is important to note too that PM decoys are not required either to train or test QSAR models [35], despite predicting exactly the same in vitro potency/affinity endpoints as SFs (e.g.…”
Section: Selecting a Scoring Function Based On Your Own Evaluationmentioning
confidence: 67%
“…For instance, a retrospective analysis based on random decoys found that a ML-based SF (MIEC-SVM) was much more predictive than a classical SF (Autodock4.2) on the ALK target, which was exactly what was later observed prospectively [8]. This is not the only ML-based SF reporting excellent prospective SBVS results without any use of PM decoys [14,34]. It is important to note too that PM decoys are not required either to train or test QSAR models [35], despite predicting exactly the same in vitro potency/affinity endpoints as SFs (e.g.…”
Section: Selecting a Scoring Function Based On Your Own Evaluationmentioning
confidence: 67%
“…Leveraging some of our recently developed programs, based on machine learning and graph neural networks, we can iteratively select synthetically feasible bioactive protease inhibitors based on bioactivity data and CANDOCK-generated pose of molecules ( Majumder et al, 2018 ; Wijewardhane et al, 2020 ). Exploration of CANDOCK efficacy on other HIV-1 targets, such as reverse transcriptase, would enable proteomic-based drug discovery, which we have shown to be useful for drug repurposing, and could lead to more potent HIV-1 therapeutics ( Chopra et al, 2016 ; Chopra and Samudrala, 2016 ; Hernandez-Perez et al, 2017 ; Majumder et al, 2017 ; Fine et al, 2019 ; Mangione et al, 2020 ; Robertson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The compound BMS-1 exhibited a strong inhibitory activity on PD-1/PD-L1 binding with an IC 50 of 91.94 nM (Figure 2B), which is consistent with the reported range (6-100 nM). [26] Without light irradiation, the prodrug did not efficiently inhibit PD-1/PD-L1 binding with an IC 50 of 12.55 μM, while the inhibitory effect was restored after light irradiation with an IC 50 (1.032 μM). IC 50 is larger than that of BMS-1, which is due to relatively low recovery efficiency of the released BMS-1 under light irradiation.…”
Section: Pd-1/pd-l1 Binding Assaymentioning
confidence: 90%